"A place to be safe, feel at home and get better": including the experiential knowledge of potential users in the design of the first wet service in Montreal, Canada - Rossio Motta-Ochoa; Natalia Incio-Serra; Hélène Poliquin; Sue-Ann MacDonald; Christophe Huỳnh; Philippe-Benoit Côté; Jean-Sébastien Fallu; Jorge Flores-Aranda (BMC, 2022)
Abstract Background The harmful use of alcohol is one of the leading health risk factors for people's health worldwide, but some populations, like people who experience homelessness, are more vulnerable to its detrimental effects. In the past decades, harm reduction interventions that target these complex issues has been developed. For example, wet services include a wide range of arrangements (wet shelters, drop-in centers, transitory housing, etc.) that allow indoor alcohol use and Managed Alcohol Programs provide regulated doses of alcohol in addition to accommodation and services. Although the positive impacts of these interventions have been reported, little is known about how to integrate the knowledge of people experiencing homelessness and alcohol dependence into the design of such programs. The aim of this study is to present the findings of such an attempt in a first wet service in Montreal, Canada. Methods Community based participatory research approach and qualitative methods-including semi-structured interviews and focus groups-were used to collect the knowledge of potential users (n = 34) of the wet service. The data collected was thematically analyzed. Results Participants reported experiencing harsh living conditions, poverty, stigmatization and police harassment, which increased their alcohol use. The intersection between participants' alcohol dependence and homelessness with the high barriers to access public services translated into their exclusion from several of such services. Participants envisioned Montreal's wet service as a safe space to drink, a place that would provide multiple services, a home, and a site of recovery. Conclusions Integrating the knowledge of potential users into the design of harm reduction interventions is essential to develop better and more adapted services to meet complex needs. We propose that it could fosters users' engagement and contribute to their sense of empower, which is crucial for a group that is typically discriminated against and suffers from marginalization.